2023
DOI: 10.1007/s11218-023-09799-7
|View full text |Cite
|
Sign up to set email alerts
|

The causalities between learning burnout and internet addiction risk: A moderated-mediation model

Abstract: This study explored how self-control and eudaimonic orientation are associated with learning burnout and internet addiction risk (IAR). Our results demonstrate that learning burnout has a significant and positive impact on IAR. The impulse system and control system play parallel mediating roles in the relationship between learning burnout and IAR. The relationship between learning burnout and IAR is moderated by eudaimonic orientation. Finally, the mediating role of the impulse system on learning burnout and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In China, 1287 migrant children between the ages of 8 to 17 were researched by Guo et al, they discovered that the detection rate of IA in migrant children was 14.3% and that there may be a connection between IA and migrant children's higher risk of depression [30]. An empirical investigation by Qin et al with 554 Chinese secondary school students ages 13 to 18 revealed a favorable correlation between LB and IA [31]. This implies that teenagers were more likely to be at increased risk of IA with a higher level of LB.…”
Section: Internet Addiction Plays a Mediating Role Between Lb And Ebp...mentioning
confidence: 99%
“…In China, 1287 migrant children between the ages of 8 to 17 were researched by Guo et al, they discovered that the detection rate of IA in migrant children was 14.3% and that there may be a connection between IA and migrant children's higher risk of depression [30]. An empirical investigation by Qin et al with 554 Chinese secondary school students ages 13 to 18 revealed a favorable correlation between LB and IA [31]. This implies that teenagers were more likely to be at increased risk of IA with a higher level of LB.…”
Section: Internet Addiction Plays a Mediating Role Between Lb And Ebp...mentioning
confidence: 99%
“…Existing research suggests that internet addiction can lead individuals to become overly reliant on the virtual online environment, 3 , 14 , 26 resulting in a sense of disconnection from real-life experiences. 3 , 27 , 28 Specifically for college students, as internet addiction intensifies, individuals may become psychologically detached from their real-life and learning environments. 6 , 29 Consequently, this detachment weakens the psychological contract between college students and their affiliated organizations (universities), eroding their sense of belonging, achievement, and confidence in the long-term benefits from these organizations.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%